Semiotic Disobedience - Sonia K. Katyal (Washington University Law Review, 2006)
Nearly twenty years ago, a prominent media studies professor, John Fiske, coined the term “semiotic democracy” to describe a world where audiences freely and widely engage in the use of cultural symbols in response to the forces of media. A semiotic democracy enables the audience, to a varying degree, to “resist,” “subvert,” and “recode” certain cultural symbols to express meanings that are different from the ones intended by their creators, thereby empowering consumers, rather than producers. In this Article, I seek to introduce another framework to supplement Fiske’s important metaphor: the phenomenon of “semiotic disobedience.” Three contemporary cultural moments in the world—one corporate, one academic, and one artistic—call for a new understanding of the limitations and possibilities of semiotic democracy and underline the need for a supplementary framework. This Article will proceed in three parts. Part I describes the phenomenon of semiotic disobedience—its history, tactics, and links to the study of language and power. Part II turns specifically to intellectual property and focuses on the law’s role in both enabling and silencing semiotic disobedience. Part III addresses the normative implications of situating semiotic disobedience within the boundaries of the First Amendment. Drawing from our jurisprudence on flag burning and symbolic speech, I argue that if intellectual property law aims to deter law-breaking, it must commit itself to honoring a much more dynamic form of semiotic democracy than currently exists.
Keywords: Symbolic speech (Law); Intellectual property; Civil disobedience; Corporate speech; Distributive justice; Democracy; Fair use (Copyright); Intangible assets; Public domain